2015
DOI: 10.1128/aac.00483-15
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Activity of Low-Amperage Continuous and Intermittent Direct Electrical Current

Abstract: Bacterial biofilms are difficult to treat using available antimicrobial agents, so new antibiofilm strategies are needed. We previously showed that 20, 200, and 2,000 A of electrical current reduced bacterial biofilms of Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa. Here, we tested continuous direct current at lower amperages, intermittent direct current, and combinations of surface materials (Teflon or titanium) and electrode compositions (stainless steel, graphite, titanium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
1
34
0
1
Order By: Relevance
“…Detachment promoted by enhanced repulsive forces between microorganisms and surface materials may also play a role (31,(35)(36)(37)(38). Although our results are consistent with previously reported data showing a bactericidal effect of DC on sessile and planktonic cells, previous studies either used different electrode positioning, focusing on biofilms grown on discs placed between two electrodes (22,25,39), or investigated the effects of custom-fabricated, electrically conductive catheters on bacterial colonization in agar plates (40). In this study, electrodes were simply placed into the lumen of commercially available catheters on which biofilms had been grown.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…Detachment promoted by enhanced repulsive forces between microorganisms and surface materials may also play a role (31,(35)(36)(37)(38). Although our results are consistent with previously reported data showing a bactericidal effect of DC on sessile and planktonic cells, previous studies either used different electrode positioning, focusing on biofilms grown on discs placed between two electrodes (22,25,39), or investigated the effects of custom-fabricated, electrically conductive catheters on bacterial colonization in agar plates (40). In this study, electrodes were simply placed into the lumen of commercially available catheters on which biofilms had been grown.…”
Section: Discussionsupporting
confidence: 39%
“…Biofilms of Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa on Teflon discs were exposed to 20, 200, or 2,000 A direct current (DC) for up to 7 days, which resulted in time-and dose-dependent antibiofilm effects, as measured by decreases in numbers of viable cells (20). Subsequent studies confirmed the microbicidal activity of continuously and intermittently applied electrical current against established biofilms of several bacterial and fungal species in vitro and in animal models (21)(22)(23)(24)(25).A potential avenue to deliver electrical current is to administer it to the lumen of catheters. This location of biofilm formation in CRBSI and CAUTI provides a site targetable by electrical current.…”
mentioning
confidence: 71%
“…epidermidis foreign body osteomyelitis exposed to 200 μA DC for 21 days had a decrease in bacterial quantities compared to those that were not exposed to current [11]. To date, we have investigated 33 different bacterial and fungal strains, representing 13 species of microorganisms, and have observed a time and dose-dependent electricidal effect against most isolates tested [12]. We have also demonstrated activity of lower amounts of DC (2, 5 or 10 μA) against most isolates tested [12].…”
Section: Introductionmentioning
confidence: 99%
“…To date, we have investigated 33 different bacterial and fungal strains, representing 13 species of microorganisms, and have observed a time and dose-dependent electricidal effect against most isolates tested [12]. We have also demonstrated activity of lower amounts of DC (2, 5 or 10 μA) against most isolates tested [12]. Additionally, we have found that the electrical current does not need to be continuously applied; for example, application of 200 μA DC for as little as 2 hours per day over a 4 day period reduces biofilms [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation